2013
DOI: 10.1590/s0103-84782013001200013
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectina e abamectina em diferentes doses e vias de aplicação contra larvas de Cochliomyia hominivorax em bolsas escrotais de bovinos recém-castrados, provenientes da região sudeste do Brasil

Abstract: RESUMO Avaliou-se a efi cácia preventiva da ivermectina e da abamectina, administradas em diferentes vias (subcutânea, intramuscular e pour-on) e doses (200 e 500mcg kg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…On the other hand, against C. hominivorax larvae, all pour‐on formulations tested (1.5 per cent ivermectin +0.5 per cent abamectin, 0.5 per cent ivermectin and 0.5 per cent abamectin), as well as 1 per cent doramectin administered subcutaneously, were considered ineffective, in two different experiments, when administered preventively against larvae of this ectoparasite. Similar results, with ivermectin and abamectin (administered through pour‐on or injectable routes), were obtained by Lopes and others (2013a, b, c). Published works that describe pharmacokinetic aspects of formulations (pour‐on and/or injectable) can elucidate the possible ineffectiveness on these cases.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, against C. hominivorax larvae, all pour‐on formulations tested (1.5 per cent ivermectin +0.5 per cent abamectin, 0.5 per cent ivermectin and 0.5 per cent abamectin), as well as 1 per cent doramectin administered subcutaneously, were considered ineffective, in two different experiments, when administered preventively against larvae of this ectoparasite. Similar results, with ivermectin and abamectin (administered through pour‐on or injectable routes), were obtained by Lopes and others (2013a, b, c). Published works that describe pharmacokinetic aspects of formulations (pour‐on and/or injectable) can elucidate the possible ineffectiveness on these cases.…”
Section: Discussionsupporting
confidence: 84%
“…microplus revealed that the pour-on combination of 1.5 per cent ivermectin +0.5 per cent abamectin showed better efficacy indexes against this ectoparasite when compared with formulations containing 0.5 per cent ivermectin, 1 per cent ivermectin and the 1 per cent abamectin+20 per cent levamisole. Using the same tick strain, Lopes and others (2013a , b , c ) diagnosed R. (B.)…”
Section: Discussionmentioning
confidence: 98%
“…The main form of treatment and control of myiasis by C. hominivorax in zootechnical animals consists of massive use of chemosynthetic insecticides, either topically or systemically [17]. Currently, there are several scientific reports on the loss of therapeutic and prophylactic efficacy of chemosynthetic insecticides to control myiasis in domestic animals [17] [20]. The indiscriminate use of these products causes high economic expenses for producers, besides offering risks to managers' and consumers' health [21].…”
Section: Impact On Animal and On Environmental Healthmentioning
confidence: 99%
“…Topical and systemic antiparasitic agents are used to control C. hominivorax larvae in bovines (Lopes et al ., 2013). Approximately 160 products are currently registered in Brazil for the control of this parasite (SINDAN, 2018).…”
Section: Introductionmentioning
confidence: 99%